The significance of cities in Islamic civilization - Mamat, Ismail (Centre for General Studies & Co-curricular Universiti Tun Hussein Onn Malaysia, 2017)
Throughout the history, cities have been the birthplaces of civilizations of mankind during the last 5,000 years. Islam was revealed to the Prophet Muhammad (peace be upon him) of the Arabian city of Makkah. He (peace be upon him) was born in that Arabian city and spent more than fifty years of his life in that city, and the rest in the city Madinah. In both cities, Islam began as a religion of da’wah and gradually spread out to the villages and desert tents of the Arabs. Thus, Islam and the nucleus of its Civilization in microcosm was formed in two cities of Makkah and Madinah. This paper aims to analyse the significance of cities in Islamic Civilization. It will also discuss on their role as the centres for Islamic da’wah and their relationship with the intellectual life. Their general patterns and structure will also be highlighted.